2009
DOI: 10.17159/2413-3108/2008/v20i4a273
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic response to exercise as measured by cardiovascular variability

Abstract: Heart rate variability (HRV), blood pressure variability (BPV) and baroreceptor sensitivity (BRS) are often used as measures of autonomic activity, even though reported results are not always comparable or as expected. It is known that endurance athletes have lower average resting heart rates than non-exercising individuals. 33,50 However, other exercise-induced autonomic influences on cardiac control are far more controversial.Autonomic control via sympathetic and parasympathetic modulation of the heart has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Heart rate variability (HRV) as an indicator of exercise-induced changes in autonomic cardiac regulation shows wide interperson SDs, as well as inconsistent study results 1 2. Vesterinen et al 3 recently reported unexplained individual adjustments in performance ability as measured by VO 2 max after exercise training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart rate variability (HRV) as an indicator of exercise-induced changes in autonomic cardiac regulation shows wide interperson SDs, as well as inconsistent study results 1 2. Vesterinen et al 3 recently reported unexplained individual adjustments in performance ability as measured by VO 2 max after exercise training.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of HRV quantification, technical aspects such as length and period of sampling times, choice of analytical techniques and non-standardisation of the populations investigated may play a role 1 4. However, little is known about the influence of preintervention physiology and genetic influence on autonomic cardiac changes, as measured by HRV, in response to exercise adaptation 4…”
Section: Introductionmentioning
confidence: 99%
“…Differing methodology and confounding factors in the studies make comparison difficult (Grant et al, 2008). The one common factor in studies showing improved HRV (increased vagal dominance) was exercise of moderate intensity (Buchheit et al, 2004;Iwasaki, Zhang, Zuckerman & Levine, 2003;Tulppo et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations are commonly used to denote these calculations: SDNN -standard deviation of all N-N intervals, RMSSD -the square root of the mean of the sum of the squares of differences between adjacent N-N intervals and pNN50 -the number of interval differences of successive N-N intervals greater than 50ms divided by the total number of N-N intervals. The pNN50 and RMSSD represent parasympathetic modulation of the sino-atrial node (Grant & Ker, 2008;Stein et al, 1999). Frequency domain analysis quantifies the variance (power) in the rhythm of the heart rates periodic oscillations, by grouping them into frequency bands viz.…”
Section: The Effect Of Exercise and Lifestyle Interventions On Heart mentioning
confidence: 99%
See 1 more Smart Citation